Treatment Planning System Commissioning of the Eclipse PBC Dose Calculation Algorithm for the Varian Clinac iX S/N 5052 - Lukarski, Dushko; Nikolovski, Dragan (Association for Medical Physics and Biomedical Engineering, 2013)
The commissioning of the Treatment Planning System (TPS) is an important part of the commissioning of a new linear accelerator (linac). In this work, we evaluated the performance of the Pencil Beam Convolution (PBC) algorithm configured for the new Varian Clinac iX (S/N 5052) at the University Clinic of Radiotherapy and Oncology in Skopje. The evaluation was performed in two stages. In the first stage, we used a workspace of the TPS itself, called “Beam Analysis”, in which the system itself calculates the depth dose and profile curves for a water phantom and compares them with those measured during the commissioning of the accelerator. In the second stage, we created, calculated and irradiated 9 test plans on a polystyrene phantom “OPERA” and measured the dose in a point with a system for absolute dosimetry and then compared the measurements with the calculations. In both stages, the results of the comparison were below 3%, in most clinically relevant cases below 2%, which indicates that the PBC algorithm can safely be commissioned for clinical use.
Keywords: TPS commissioning; PBC algorithm; Eclipse TPS